Study of kinetic parameters for the catalytic cracking process in Y type aerosol catalyst - Glikina, Irene; Glikin, Marat; Kudryavtsev, Sergey (Eastern-European Journal of Enterprise Technologies, 2017)
At present, in the petroleum refining industry, catalytic cracking is carried out on the heterogeneous zeolite-containing or aluminosilicate supported catalyst. A well-known deficiency of supported catalyst is the blockage of pores by coke. A aerosol nanocatalysis technology is proposed as the solution to this problem. The basic principle of this technology is complete exclusion of the use of a support from the industrial practice. In this case, the catalyst particles in the process of chemical transformation reach nano dimensions due to the mechanochemical treatment of particles. As a result, we observed an increase in the reaction rate, a decrease in the concentration of catalyst and the time of contact, as well as a rise in productivity by the basic component. The basic principle of the aerosol nanocatalysis technology makes it possible to successfully repeatedly return the catalyst to the reactor. It is established that the use of zeolite-containing catalysts (type Y) in the form of aerosol does not decrease productivity of the process of catalytic cracking of vacuum gas oil. In this case, an increase in the reaction rate and selectivity is observed. It was found that the temperature and the oscillation frequency make it possible to control the progress of chemical transformation under conditions of AnC technology. The process of catalytic cracking under conditions of AnC technology could be proposed for the implementation either in parallel to the acting installations or as the independently operated unit for small-scale refineries.